Effects of Peppermint Aromatherapy in Cardiovascular Disease Patients: A Literatur Review - Chaera Maya Sari; Tuti Herawati; Chiyar Edison Sunarya (UIMA Press, 2023)
Background: Cardiovascular disease is a non-infectious disease that causes a high mortality rate in the world. The complementary medication reduces symptoms related to cardiovascular disease such as anxiety, stress, sleep quality, fatigue, pain, anxiety, depression, nausea and vomiting. The medication is also to improve the life quality of the patients. Aromatherapy is one of the complementary therapies known as Complementary and Alternative Medicine (CAM) to reduce or relieve symptoms of various diseases and conditions including cardiovascular disease. Peppermint aromatherapy has a refreshing cold aroma that creates a feeling of comfort. Objectives: To identify the effectiveness of peppermint aromatherapy in improving several conditions, such as anxiety, stress, sleep quality, fatigue, and pain in patients with cardiovascular disease. Methods: The method uses a literature review with the PRISMA approach with a study database selection process consisting of ClinicalKey, ClinicalKey Nursing, Embase, Pro Quest, Sage Jornal, Science Direct, Scopus, and Springer Link using the keywords peppermint aromatherapy and cardiovascular disease patients. Results: Based on a review and review of five selected journals, it was found that peppermint aromatherapy helps improve cardiovascular disease disorders through its analgesic, anxiolytic, sedative and sleep enhancing properties. Conclusion: Cardiologists can use peppermint aromatherapy as an alternative therapy to reduce fatigue, pain, anxiety, nausea, vomiting and improve sleep quality in patients with cardiovascular disease.